EphA2 modulates radiosensitive of hepatocellular carcinoma cells via p38/mitogen‐activated protein kinase‐mediated signal pathways. Issue 10 (9th October 2015) - Jin, Qiao; Li, Xiangjun; Cao, Peiguo
Abstract: This experiment was conducted to investigate the role of EPH receptor A2 (EphA2) in the modulation of radiosensitivity of hepatic cellular cancer (HCC) cells and to determine whether p38/mitogen‐activated protein kinase (p38MAPK) signaling mediated EphA2 function in this respect. The protein expressions of EphA2 and phosphorylated p38MAPK were tested in HCC and normal hepatic tissues. In HCC 97H cells, EphA2 was overexpressed and knocked out by transfection with EphA2 expression vector and EphA2‐ShRNA, respectively, prior to cell exposure to low‐dose irradiation. Significantly upregulated EphA2 and phosphorylated p38MAPK were observed in HCC tissues, compared with those in normal hepatic tissues. Low‐dose irradiation (1 Gy) only caused minor damage to HCC 97H cells, as assessed by alterations in cell viability, apoptosis rate, and cell healing capacity ( p = 0.072, p = 0.078, and p = 0.069 respectively). However, EphA2 knock‐out in HCC 97H cells induced significant reduction in cell viability and cell healing capacity after these cells were subjected to low‐dose irradiation. Apoptosis rate underwent dramatic increase ( p < 0.01). By contrast, EphA2 overexpression in HCC 97H cells reversed these effects and enhanced cell colony formation rate, thus displaying remarkable attenuation of radiosensitivity of HCC 97H cells. Further, SB203580, a specific inhibitor of p38MAPK, was added to HCC 97H cells over‐expressing EphA2. The effect of EphA2 overexpression on the radiosensitivity of HCC 97H cells was abrogated. Thus, the present study indicates that EphA2 have the ability to negatively regulate the radiosensitivity of HCC 97H cells, which mainly depends on 38MAPK‐mediated signal pathways.